Beyond 'Kerasukan': Integrating Traditional Beliefs with Modern Psychiatric Frameworks in Indonesia’s Mental Health Discourse - Gumilang, Rangga Prawira; Cahyaningrum, Ratnasari; Wiranata, Made Adi (Indonesia Discourse, 2025)
In many Indonesian communities, mental health crises are frequently interpreted through the lens of spiritual possession (kerasukan) or supernatural intervention. This study explores the discursive gap between traditional healing practices and modern psychiatric frameworks. Through a qualitative multi-sited ethnography involving spiritual healers (dukun), psychiatrists, and families of patients in Java and South Sulawesi, the research investigates how pluralistic health-seeking behaviors are negotiated. The results reveal that while clinical psychiatry is increasingly accessible, patients often prefer a hybrid approach that addresses both biological symptoms and spiritual anxieties. The study identifies "cultural translation" as a critical missing link in Indonesia’s public health policy, where psychiatric interventions often fail due to a lack of engagement with local ontological beliefs. By proposing a collaborative model of "culturally-informed psychiatry," this research contributes to the global discourse on decolonizing mental health. It argues that recognizing the validity of cultural idioms of distress is essential for improving treatment adherence and reducing the stigma associated with mental illness in non-Western contexts.